2016
DOI: 10.1155/2016/3058015
|View full text |Cite
|
Sign up to set email alerts
|

Right Atrial Clot Formation Early after Percutaneous Mitral Balloon Valvuloplasty

Abstract: Mitral balloon valvuloplasty which has been used for the treatment of rheumatic mitral stenosis (MS) for several decades can cause serious complications. Herein, we presented right atrial clot formation early after percutaneous mitral balloon valvuloplasty which was treated successfully with unfractioned heparin infusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Nonetheless, in this case, we showed that anticoagulant therapy with enoxaparin, followed by warfarin, completely resolved the existing clot and obviated the subsequent need for surgery. Ateş et al 2 reported the same incidence in a 40-year-old patient referred for PBMV. The case was successfully treated within 24 hours of unfractionated heparin infusion.…”
Section: Discussionmentioning
confidence: 61%
See 4 more Smart Citations
“…Nonetheless, in this case, we showed that anticoagulant therapy with enoxaparin, followed by warfarin, completely resolved the existing clot and obviated the subsequent need for surgery. Ateş et al 2 reported the same incidence in a 40-year-old patient referred for PBMV. The case was successfully treated within 24 hours of unfractionated heparin infusion.…”
Section: Discussionmentioning
confidence: 61%
“…Nevertheless, complications such as hemopericardium, cardiac rupture, cardiac tamponade, and last but not least clot formation have also been reported after PBMV. 2 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations